Midwifery Care for Menopausal Women with Hypertension through Beet Juice Therapy at the Ujung Kubu Community Health Center - Fitri Andriani; Avira Mutia Anjani Marpaung (Jurnal EduHealth, 2025)
Menopause increases the risk of hypertension in women due to a decrease in estrogen hormones, which affects blood vessel elasticity. This study aims to describe the implementation of midwifery care for menopausal women with hypertension through the application of beet juice therapy as a complementary therapy. The research method used was qualitative with a descriptive case study design on one subject (Mrs. L, 55 years old) with grade 1 hypertension in the working area of the Ujung Kubu Community Health Center. Care was provided using Varney's midwifery management and SOAP documentation, with the intervention of administering 250 ml of beet juice per day for seven consecutive days. The results showed a significant decrease in blood pressure, from an initial reading of 160/100 mmHg to 140/85 mmHg after the intervention. In addition to clinical improvement, the subject also reported improvement in subjective complaints such as reduced dizziness, anxiety, and improved sleep quality. This reduction in blood pressure is supported by the natural nitrate content in beetroot, which is converted into nitric oxide to aid vasodilation of blood vessels. The conclusion of this study is that beetroot juice therapy has the potential to be an effective, safe, and economical non-pharmacological alternative therapy in midwifery care to help control blood pressure in menopausal women